Assessment Of Airborne Particulate Matter And Radioactivity At Qassim, Saudi Arabia - O, Alnagran Hamed Mohammed (2023)
Epidemiological and toxicological research has shown a close connection between particulate matter (PM) with respiratory and cardiovascular disorders. Thus, PM in the air we breathe is detrimental to human health. Numerous nations have conducted in-depth study on the problem of PM and related health and environmental issues. Therefore, this study describes the radioactivity, physical and chemical properties of PM in Qassim. This research focuses on radioactive particle, which in turn impact the environmental comportments of the related radionuclides. PM of size less than 2.5 microns in aerodynamic diameter (PM2.5) and PM less than 10 microns in aerodynamic diameter (PM10) concentrations have been measured during the period of July 2020–June 2021 in the central urban and rural areas of Qassim. In urban Qassim, the average PM concentration were 33.16 μg/m3 and 155.38 μg/m3 for PM2.5 and PM10, respectively. In rural Qassim, the PM concentrations were 23.03 μg/m3 and 93.57 μg/m3, respectively. A total of 18 elements were determined and identified, and their concentrations in (mg/kg) were compared to literature. Natural radioactivity levels of 226Ra, 232Th, and 40K in 276 samples were evaluated using sodium iodide (NaI) detector. Ra-226 activity concentration ranged from 10.01 to 47.60 Bq/kg with an average of 350.00 ± 0.06 Bq/kg. 232Th ranged from 11.30 to 44 Bq/kg, with an average of 32.00 ± 0.40 Bq/kg. 40K ranged from 115.10 to 454.80 Bq/kg with an average of 294.99 ± 1.31 Bq/kg. Gamma-ray hazard levels were calculated using a variety of methods, including the Radium equivalent with an average of 104.37 Bq/kg, internal and external hazard indices with an average of 0.28 and 0.38 respectively,